Borders and Bridges – Boundaries as an Opportunity - Stefano Follesa; Francesco Armato; Sabrina Cesaretti; Yao Peian (Journal of Systemics, Cybernetics and Informatics)

(untitled)
The boundary is an ephemeral concept, an imaginary line that marks the terms of a territory. The term boundary is related to the concept of limit that indicates both a sign not to be exceeded and, by extension, a value that conditions a behavior or a performance. The Italian word "confine" that means boundary comes from the Latin cum-finis; the etymology of the term indicates something that separates but, at the same time, that unites, something that has an end but that creates the presuppositions for something else. The border, therefore, is not only a limit but an opportunity; crossing the border is a gesture that gives us the awareness that nothing is taken for granted, immutable and that everything can change in the relationship with otherness. Cultural wealth is built first in a direct relationship with the material and immaterial resources of a place but also through "contaminations" that come from external knowledge and are acquired and made their own through a local reinterpretation. Globalization has cut the threads of such contaminations, drying the sources of diversity in the project and giving us back the shared universal languages that guide the aesthetics of objects. The recent pandemic has shown us how the creation of virtual connections has contributed to enrich the scenarios of research by giving it a multiplicity of views. The same mode can be used for applied research. Borders and Bridges is a pilot project of exchange between international universities that is born with the aim of developing practices of transdisciplinary cultural contamination in the context of an exchange through the internet between international universities. The design discipline has in its D.N.A the ability to connect and develop proposals that create synthesis between the vision of project activities and that of social sciences. The idea of the project is to work on borders as lines of opportunity for the elaboration of elements of innovation through the tools of the design discipline. The dual objective is, on the one hand, to promote new methods of exchange in the educational field, and on the other to promote the encounter between cultural systems. The design, in fact, is free from borders, "has always had the ability to look at different fields and disciplines favoring cross-contamination" (Cappellieri A. Tenuta L. 2019).